A SYSTEMIC APPROACH TO DECARBONIZATION OF REGIONAL ENERGY: FROM METHODOLOGY TO PRACTICE - NIKITIN, YEVGENII; SHPAK, OLEKSANDR; MALIARENKO, OLENA; YEVTUKHOVA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper explores the scientific, methodological and applied foundations of the development and implementation of regional energy plans (REP) as a key tool for decarbonization and energy transformation of Ukraine. Using the example of Khmelnytskyi region, regional features of energy consumption are analyzed, strengths and weaknesses, opportunities and difficulties in the implementation of renewable energy sources (RES) are identified. Scientific and applied problems related to the integration of RES, the lack of a unified system of regional energy management, insufficient coordination between energy supply sectors and the need for unified tools for assessing the socio-economic effect are formulated. Methodological foundations for the development of REP are proposed. The main conceptual provisions of the development of a regional energy plan are a holistic approach to individual sectors of energy planning, maximum consideration of regional characteristics, involvement of all stakeholders in the development of the plan, creation and provision of conditions for the stable functioning of the regional energy management system. The practical results of the research are presented in the form of projects to improve the energy efficiency of regional facilities, use of waste heat from nuclear power plants for heat supply, creation of university micro-energy systems (microgrids), introduction of biofuel technologies and solar power plants. Their technical and economic efficiency and the possibility of scaling to other regions of Ukraine are substantiated. The proposed approaches and results can serve as the basis for the formation of regional strategies for sustainable development, increasing investment attractiveness and achieving national decarbonization goals.